2008
DOI: 10.1038/nature07396
|View full text |Cite
|
Sign up to set email alerts
|

BAX activation is initiated at a novel interaction site

Abstract: BAX is a pro-apoptotic protein of the BCL-2 family stationed in the cytosol until activated by a diversity of stress stimuli to induce cell death. Anti-apoptotic proteins such as BCL-2 counteract BAX-mediated cell death. Although an interaction site that confers survival functionality has been defined for anti-apoptotic proteins, an activation site has not been identified for BAX, rendering its explicit trigger mechanism unknown. We previously developed Stabilized Alpha-Helix of BCL-2 domains (SAHBs) that dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
770
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 630 publications
(816 citation statements)
references
References 50 publications
38
770
2
6
Order By: Relevance
“…The recent determination of the structure of a Bax/ BimBH3 peptide complex reinforces the direct activation theory (Gavathiotis et al, 2008). It is interesting that the constrained BH3 peptide was found to interact with a site involving helices a1 and a6, different from the canonical binding groove characterized for pro-survival proteins.…”
Section: S131mentioning
confidence: 64%
See 1 more Smart Citation
“…The recent determination of the structure of a Bax/ BimBH3 peptide complex reinforces the direct activation theory (Gavathiotis et al, 2008). It is interesting that the constrained BH3 peptide was found to interact with a site involving helices a1 and a6, different from the canonical binding groove characterized for pro-survival proteins.…”
Section: S131mentioning
confidence: 64%
“…In addition, they reported that Bax/Bak mutants, which were unable to bind Bcl-2, Bcl-xL and Mcl-1, were not constitutively activated, suggesting that they are not directly repressed by the pro-survival proteins and require additional steps to activate them (Kim et al, 2006b). A few weeks ago, the first NMR structure of a constrained Bim BH3 peptide bound to Bax was published, providing one more argument that Bax may be activated by the direct binding of Bim (Gavathiotis et al, 2008).…”
Section: S130mentioning
confidence: 99%
“…Interestingly, whereas both proteins form large permeability pores in their respective target membranes, their mechanism of activation is entirely different. Whereas GSDMD is activated by proteolytic cleavage, Bax is activated by interactions within the Bcl‐2 family of proteins (Gavathiotis et al , 2008; Czabotar et al , 2013). A strong difference can also be expected for the atomic structure of the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…17 40 It remains unclear whether binding of BH3-only proteins to the pro-survival BCL-2-like proteins or their direct binding to BAX/BAK is more critical for the initiation of apoptosis. 37,38,41 It is, however, clear that some of the BH3-only proteins are more potent inducers of apoptosis (e.g., BIM, PUMA, tBID) than others (e.g., BAD, NOXA, BMF). Pertinently, the potent BH3-only proteins bind avidly to all prosurvival BCL-2 family members and can also engage BAX/ BAK, whereas the less potent ones have more select binding specificities for the pro-survival BCL-2 family members and reportedly do not bind to BAX or BAK.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%